Pengaruh Brand Image Terhadap Brand Equity Yang Dimediasi Oleh Brand Awareness (Studi Deskriptif Kuantitatif pada Pendengar Solo Radio FM di SMA Negeri 2 Surakarta) - Sugiyarti, Sugiyarti, Drs. Joko Sutarso, S.E, M.Si, Monika Sri Yuliarti, S.Sos., M.Si (2015)
Establishment of a brand image is critical in the effort to build brand equity. For images that are captured, unwitting, and trusted by consumers. The purpose of this study was to describe the influence of brand image on the formation of brand awareness and brand equity in FM Radio listeners Solo Surakarta. The research method used explanatory research. The population in this study were all students of SMAN 2 Surakarta. The number of samples taken in this study of 60 people (respondents). Aside from using quota sampling technique. Test research instrument validity and reliability. Data were analyzed using path analysis (path analysis). The results showed that: 1) Brand image has positive influence on brand awareness. The first hypothesis testing results gained by 3.632 tcount accepted at 5% significance level (p <0.05) and H1 accepted. That is, the better the image of the brand, the higher the brand awareness of the respondents; 2) Brand image has positive influence on brand equity. Results of testing the second hypothesis gain of 6.963 tcount accepted at 5% significance level (p <0.05) and H2 accepted. That is a unique brand image, strong and preferably will bring the brand to be in a strategic position in the memory of consumers to increase brand equity; 3) Brand awareness effect on brand equity. The third hypothesis testing results gained by 2.517 tcount accepted at 5% significance level (p <0.05) and H3 accepted. This means that if there is an increase in brand awareness led to an increase in brand equity